(untitled) (International Journal of Physiotherapy, 2017)
Background: Rotator cuff tendinopathy is a significant problem among diabetics that frequently restricts patient’s activity in terms of pain and disability. The purpose of this study was to compare between the effect of Astym therapy and kinesiotaping in treating diabetic patients with chronic rotator cuff tendinopathy. Methods: 56 diabetic patients diagnosed with chronic rotator cuff tendinopathy were randomly assigned into Astym therapy group (n=28) or kinesiotaping group (n= 28). All patients received conventional program in addition to Astym treatment or Kinesiotaping for 24 sessions (2times/week). Patients were assessed at baseline and at the end of corresponding intervention with visual analogy scale (VAS) for pain intensity, shoulder disability questioner (SDQ) for shoulder disability, and electrogoniometer for shoulder range of motion. Results: For the 56 study participants (21 males and 35 females; mean age=41.9±6.9) years there were significant differences in all measuring outcomes in both group when compared to baseline measurements (p<0.05). Post treatment comparison showed a significant reduction in pain score in favour of kinesio taping group with no significant differences in SDQ score or active shoulder range of motion between the two groups (p > 0.05). Conclusion: kinesiotaping appears to be more effective than Astym therapy in reducing pain for diabetic patients with chronic rotator cuff tendinopathy.